(3beY GdfahS hQbjI GdeCfhSs - (3CHh HcQ Hf eMeO Hf YHO GdeDef Hf nMpQjR Hf eYnqdj GdMSjfj GdMUfj, Jbqj GdOjf,J (B829 (3g` s ((3Ndjd Hf GdCNfGei GdSYOfi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdehLhOGJ ef XdeI GdYOe hHYO aEf GdfGS cGfhG ai GdLGgdjI LgdkG hYejg YejG MJi LGA GdMdb hRgb GdHGWd Ef GdHGWd cGf RghbG s
(3BNQgG (B:s
(3hfNJe gPG GdcJGH Hbhd UGMH SjO GdChdjf hGdGNQjf Udi Gddg Ydjg hSde CHj GdOQOGA QVi Gddg Yfg deG ONd GdTGe bGd jG Cgd GdTGe ESeYhG bhd CN fGUM dce eGdi CQGce JHfhI eG dGJScfhf JLeYhf eG dG JCcdhf Cf GdPjf cGfhG bHdce HfhG eSOkG hCedhG HYjOkG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B69 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B74s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs